1999
DOI: 10.1093/humrep/14.5.1243
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy rates after in-vitro fertilization in cases of tubal infertility with and without hydrosalpinx: a meta-analysis of published comparative studies

Abstract: This meta-analysis was intended to evaluate differences in pregnancy rates after in-vitro fertilization (IVF) in tubal fertility with and without hydrosalpinx. It examined nine published retrospective comparative series and five series published as abstracts for which additional information was obtained. In all, these studies involved 5592 patients (1004 with hydrosalpinx and 4588 with tubal infertility without hydrosalpinx). The main outcome measures were rates of pregnancy, implantation, live delivery, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
125
0
12

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(141 citation statements)
references
References 26 publications
3
125
0
12
Order By: Relevance
“…Women with hydrosalpinges have decreased implantation rates in IVF, and their pregnancy rates can be improved with salpingectomy before IVF. The hydrosalpinx generates an inflammatory fluid that may interfere with endometrial receptivity and embryonic implantation mechanically or chemically (Zeyneloglu et al 1998;Camus et al 1999). Although a study has shown that culturing mice embryos in the medium containing hydrosalpinx fluid can suppress embryo maturation and promote degeneration, this toxic effect does not affect human embryos.…”
Section: Hox Genes and Hydrosalpinxmentioning
confidence: 99%
“…Women with hydrosalpinges have decreased implantation rates in IVF, and their pregnancy rates can be improved with salpingectomy before IVF. The hydrosalpinx generates an inflammatory fluid that may interfere with endometrial receptivity and embryonic implantation mechanically or chemically (Zeyneloglu et al 1998;Camus et al 1999). Although a study has shown that culturing mice embryos in the medium containing hydrosalpinx fluid can suppress embryo maturation and promote degeneration, this toxic effect does not affect human embryos.…”
Section: Hox Genes and Hydrosalpinxmentioning
confidence: 99%
“…Hydrosalpinx [1,2,3], pelvic inflammatory disease, and bacterial infection [4], as well as smoking habits [5,6], are known to be negative influencing factors. Furthermore, a previous (tubal) ectopic pregnancy (TEP) [7,8] and surgery [5] affect the fertility of women.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms which had been suggested were either direct or systemic influenced by inflammatory mediations on the developing embryo in uterus or on the endometrium prior to or during implantation. It was suspected to have toxic effect on embryo development and interfere the implantation of embryos, and resulted in decreaseing pregnancy rate (8)(9)(10)(11). Most relative studies which revealed ECF with hydrosalpinges will have negative effect on pregnancy rate (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…It was suspected to have toxic effect on embryo development and interfere the implantation of embryos, and resulted in decreaseing pregnancy rate (8)(9)(10)(11). Most relative studies which revealed ECF with hydrosalpinges will have negative effect on pregnancy rate (9)(10)(11). The more extensive the hydrosalpinx, the lower the implantation rates (12).…”
Section: Introductionmentioning
confidence: 99%